More than a Game : The Best of Alf Van Hoose - Van Hoose, Alf, 1920-1997 (Book collections on Project MUSE., 2009)
The best work of one of Alabama's longest-serving and most beloved sports journalists. Although he spent 43 years at the same job, Alf Van Hoose was not a man limited by the boundaries of his profession. As Birmingham News sports editor for 21 years and a columnist for a decade before that, Van Hoose helped define a city, a state, and a region largely known for sports. He was the writer of record for some of the biggest sporting events and personalities in the state of Alabama in the last half of the 20th Century. Wayne Hester, Van Hoose's successor as sports editor of The News, in 1990, said.